Electrochemical studies of ochratoxin a mycotoxin at gold electrodes modified with cysteamine self-assembled monolayers. Its ultrasensitive quantification in red wine samples - Perrotta, Patricio Rene (2011)
The quantification of ochratoxin A is studied at cysteamine self-assembled monolayer modified gold electrodes in red wine samples by square wave voltammetry. Detection and quantification limits of 0.004μg L-1 and 0.012μg L-1, respectively, were determined. The recovery percentages were in the range from 146% to 94.0% at spiking levels ranging from 0.02 to 5μg L-1. The variation coefficients for within-laboratory repeatability varied from 31.4 to 11.5% for spiked level from 0.02 to 2.0μg L-1. The developed electrochemical method is efficient, reproducible, and ultrasensitive for the quantification of OTA in red wine samples.